The RECONSTRUCTION of PLURALISTIC ISLAMIC EDUCATION - Amrizal Amrizal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
This article seeks to explore a model of learning having pluralistic paradigm, that is a learning which is based on the basic principle that acknowledges and accepts the religious and cultural differences as the consequence from the plural society. This model of learning aims at creating attitude and life consciousness among Muslim students in order to respect other religions as the implementation of religious tolerance. It is related to respecting the plurality of religions, cultures, races and social and economic groups in the society, showing the love and sincerity among human beings and environment as God’s creation and respecting the differences of idea in practicing religious rituals.